World Class University pada Perguruan Tinggi Keagamaan Islam: Kebijakan dan Strategi Transformasi - Ali Mufron (LP2M Sekolah Tinggi Agama Islam Nahdlatul Ulama Pacitan, 2021)
The purpose of this study is to understand and determine the direction of policies and strategies for the transformation of the Islamic Religious College Perguruan Tinggi Keagamaan Islam (PTKI) into a World Class University (WCU). The method used by the writer in this research was literature, through primary data by reading primary books. This study involved colleagues, lecturers of Islamic education management from various campuses, with the following steps: testing the manuscript through discussion, criticism, suggestion, improvement, and finalization. Based on the results of the study, it is concluded that PTKI in its efforts to become a WCU must be able to lay a strong basis through the development of the character of educators and educational staff who have academic ethics with rational, objective and normative characteristics. Those academic ethics must be fundamental elements of morality in facing social, economic, political, cultural and science and technology developments.